Loss of MMP-2 in murine osteoblasts upregulates osteopontin and bone sialoprotein expression in a circuit regulating bone homeostasis - Rebecca A. Mosig; John A. Martignetti (The Company of Biologists, 2013)
SUMMARY Multicentric osteolysis with arthropathy (MOA; MIM 605156) is an inherited osteolyses and arthritis syndrome resulting from loss of matrix metalloproteinase 2 (MMP-2). We recently demonstrated that Mmp2-/- mice represent a unique model for the study of the human disease, sharing many features of the human syndrome including skeletal dysplasia and defects in osteoblast behavior. We therefore sought to explore the secondary molecular effects of MMP-2 loss, which coexist with the underlying skeletal and osteoblast phenotypes. We used quantitative real-time RT-PCR (qRT-PCR) to measure osteoblast-related gene expression through ex vivo osteoblast differentiation of bone marrow stromal cells (BMSC) from Mmp2−/− and Mmp2+/+ mice. We used western blot to measure osteopontin (OPN) serum levels and immunohistochemical staining to examine bone expression. MMP-2 expression was inhibited in SaOS2 cells using siRNA, and decreased MMP-2 expression at both RNA and protein levels was confirmed by qRT-PCR and western blot, respectively. Mmp2−/− BMSC induced to differentiate into osteoblasts were shown to significantly upregulate OPN and bone sialoprotein (BSP) expression levels compared with controls. Transcriptional upregulation was maintained in vivo, as demonstrated by increased levels of OPN in serum and bone in Mmp2−/− mice. These effects are generalizable because siRNA-mediated inhibition in cultured cells also upregulated OPN and BSP. OPN and BSP are known to affect MMP-2 expression and activity but have not previously been shown to be regulated by MMP-2. Identification of this newly defined circuitry provides insight into the potential molecular landscape underlying the MOA phenotype and highlights a pathway that might play a role in normal bone homeostasis.